GEOMAGNET DAN HUBUNGANNYA DENGAN KONFIGURASI STRUKTUR GEOLOGI BAWAH PERMUKAAN CEKUNGAN PATI BAGIAN SELATAN, JEPARA, JAWA TENGAH - -, Andi Agus Noor (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
The Area of Southern part of Pati Basin located in, Jepara Regencyt, Central Java Province was a frontier area. Because of that will held a further research to know about geological condition at this area especially about the subsurface structure geology.In this area expand some phenomena of Quaternary Geology such a fault, earthquake and volcanism, with active and re-activated activities. The regional structure influences on forming the smaller faults and volcanism Quaternary. The faults are Tayu Regional Fault (L-1) with northwest - southeast direction, Rahtawu Fault (L-2) with north – south direction, and Jepara and Bangsri Fault (L-3) with southwest – norteast directions. This regional structure experience the reactivated, and cross the bedrock. The product of this process is magma came out from the crust and formed the volcanism.Based on result of geomagnet interpretation record on territorial waters of Muria Peninsula (Pati’s Bain South’s part) show the existence of breaking structure at Trajectory L-1,L2 and L-3. Predicted by the fault structure is effect from continuity of structures which there are in land